Tracing the Rules of Sexual Abnormality in the Islamic Jurisprudence - Hannani; Hammad, Hamza Abed Al Karim; AR, Zulfahmi (Universitas Islam Negeri Alauddin Makassar, 2023)
Sexual abnormality or deviation is a social disorder that is considered a violation of social norms and expectations of civility. Such behavior is deemed deviant because it goes against religious rules and values upheld by society. This research aims to establish a middle ground between sexual deviation and Islamic jurisprudence with regard to sexual deviation activities. To achieve this, a comprehensive review of linked data sources was conducted using qualitative and literary research. The findings showed that certain types of sexual deviance such as sadomasochism, exhibitionism, voyeurism, fetishes, and others have not been extensively discussed in fiqh books. According to the rules of Uşul Fiqh,